Pengaruh Kurs, Inflasi, Dana Pihak Ketiga (DPK), Pendapatan Bank, Capital Adequecy Ratio (CAR), Dan Non Performing Financing (NPF) Terhadap Tingkat Pengguliran Dana Bank Umum Syariah Non Devisa Periode 2014-2018 - Lisa Marlina JN; Mia Angelina Setiawan (Universitas Negeri Padang, 2019)
This reseach aims to obtain empirical evidence of the effect of Exchange Rate, Inflation, Third Party Funds (TPF), Bank Revenues, Capital Adequacy Ratio (CAR), and Non Performing Financing (NPF) on Fund Revolving Levels in Non-Foreign Islamic Commercial Banks in Indonesia for the period 2014-2018. Data is obtained from quarterly financial reports taken from the website of each Non-Foreign Exchange Islamic Bank. The dependent variable in this study is the Fund Revolving Levels and the independent variables are the Effect of Exchange Rate, Inflation, Third Party Funds (DPK), Bank Revenues, Capital Adequecy Ratio (CAR), and Non Performing Financing (NPF). The result of this study is that the exchange rate has a positive and not significant effect on the Fund Revolving Levels of sharia bank. The inflation has a positive and significant effect on the Fund Revolving Levels of sharia bank.. The third party funds have a negative and significant effect on the Fund Revolving Levels of sharia bank. And than bank income, Capital Adequacy Ratio (CAR), and Non Performing Financing (NPF) have a negative and insignificant effect on the Fund Revolving Levels of sharia bank